1999
DOI: 10.1083/jcb.146.4.709
|View full text |Cite
|
Sign up to set email alerts
|

Mcm2, but Not Rpa, Is a Component of the Mammalian Early G1-Phase Prereplication Complex

Abstract: Previous experiments in Xenopus egg extracts identified what appeared to be two independently assembled prereplication complexes (pre-RCs) for DNA replication: the stepwise assembly of ORC, Cdc6, and Mcm onto chromatin, and the FFA-1–mediated recruitment of RPA into foci on chromatin. We have investigated whether both of these pre-RCs can be detected in Chinese hamster ovary (CHO) cells. Early- and late-replicating chromosomal domains were pulse-labeled with halogenated nucleotides and prelabeled cells were sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
167
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 159 publications
(195 citation statements)
references
References 67 publications
28
167
0
Order By: Relevance
“…We show that indeed as expected, Killin always adopts a mutually exclusive punctuated nuclear expression pattern with the 2 important accessory proteins in DNA replication. [19][20][21][22][23] Furthermore, we also notice that in non-S-phase cells, RFP-Killin congregates in the nucleolus where rRNA transcription is known to be most active. 24 We provide evidence that throughout the cell cycle, RFPKillin is tightly associated with the nucleic acids.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…We show that indeed as expected, Killin always adopts a mutually exclusive punctuated nuclear expression pattern with the 2 important accessory proteins in DNA replication. [19][20][21][22][23] Furthermore, we also notice that in non-S-phase cells, RFP-Killin congregates in the nucleolus where rRNA transcription is known to be most active. 24 We provide evidence that throughout the cell cycle, RFPKillin is tightly associated with the nucleic acids.…”
Section: Introductionmentioning
confidence: 85%
“…23,[25][26][27] To complement the analysis of the nuclear co-localization of Killin and RPA during S phase described above, expression vectors encoding GFP-PCNA and RFP-Killin were transiently co-transfected into exponentially growing Cos-E5 cells. Twenty-four hours following the transfection, confocal fluorescent microscopy revealed that, like RPA, PCNA also exhibited a mutually exclusive nuclear localization pattern with RFP-Killin (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…All experiments were performed in triplicate and images shown are representative examples. Immunofluoresence, to detect BrdU incorporation, was performed as described (Dimitrova et al, 1999). Antibodies used were p300 N-terminal (N-15) p300 C-terminal (C-20), CBP (A-22), p53 (DO-1), RB, (C-15), RB (IF8), c-myc (9E10) (Santa Cruz Biotechnologies, Santa Cruz, USA); p21 WAF1 (Ab-1) (Oncogene Research Products, San Diego, USA); phospho-RB (Ser807/ 811), pan-acetyl-lysine (monoclonal) (Cell Signalling Technologies, Hitchin, UK); cyclin A (6E6), cyclin D1 (P2D11F11), cyclin E (G2a), mcm2 (G1) (Novocastra, Newcastle-upon-Tyne, UK); b-actin (AC-15) (Abcam, Cambridge, UK); fluorescein isothiocyanate (FITC)-BrdU (N1031) (BD Biosciences, Oxford, UK); and BrdU (Cell Proliferation Kit) (Amersham, Pollards Wood, UK).…”
Section: Immunoblotting Immunoprecipitation and Immunofluorescencementioning
confidence: 99%
“…We next reasoned that, on the other hand, some consequences on the abnormal retention of the CldUsubstituted DNA around BCL6 bodies can be revealed using the reverse order (first CldU, then IdU) (Dimitrova et al, 1999;Ma et al, 1998). Thus, in a second set of experiments, cells were labeled for either 15 or 90 minutes with CldU, chased for 6 hours, and pulsed again for 15 minutes with IdU.…”
Section: Concomitant Visualization Of Replicating Andmentioning
confidence: 99%
“…In some experiments (e.g., in Fig. 5C), the cells were exposed to CSK buffer containing 0.5% Triton X100 for 5 minutes on ice just prior to the fixation to remove the soluble fraction of PCNA presumably not linked to replication (Dimitrova et al, 1999). Goat antirabbit Alexa 488, goat anti-mouse Alexa 596, goat antirat Alexa 596 and goat anti-rat Alexa 547 (Interchim) were used as secondary antibodies according to the primary antibodies used.…”
Section: Detection Of Halogenated Dna At Optical Levelmentioning
confidence: 99%